2022
DOI: 10.13177/irpa.a.2022.18.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Ákvörðun þolenda ofbeldis að tilkynna brot til lögreglu

Abstract: As most crimes are never reported, official police data underestimates the true extent of crimes. Decisions to report also varies between groups resulting in a systematic bias in data used to form police changes in the criminal justice system. The current research focuses on the impact that crime types, victims SES, and trust towards the police has on decisions to report. The study uses a combined dataset of victimization surveys conducted annually from 2014 to 2021 (n = 19,440). Results show that fewer victim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Thematic analysis of the interviews revealed that participants generally had a negative experience of testifying in court. Most participants reported a lack of control during their court proceedings, perhaps partially due to their legal position as a witness in their criminal case with limited informational and procedural rights (Antonsdóttir, 2019). Participants frequently reported that they had felt small, insignificant, and stressed during their court hearings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thematic analysis of the interviews revealed that participants generally had a negative experience of testifying in court. Most participants reported a lack of control during their court proceedings, perhaps partially due to their legal position as a witness in their criminal case with limited informational and procedural rights (Antonsdóttir, 2019). Participants frequently reported that they had felt small, insignificant, and stressed during their court hearings.…”
Section: Discussionmentioning
confidence: 99%
“…2 In fact, concerns about public exposure is one of the reasons women may be reluctant to report violence to the police (Jones et al, 2009). Before the legislative amendments, complainants did not have the right to sit in closed court hearings and observe the proceedings after giving testimony (Antonsdóttir, 2019). Now, however, complainants have the right to sit in court after giving their testimony, and their legal rights protector has the right to submit additional evidence and ask additional questions from the accused and witnesses after questioning by the prosecutor and the defense lawyer.…”
Section: Icelandic Criminal Court Proceduresmentioning
confidence: 99%